Management of Plant-Parasitic Nematodes in Florida Peanut Production - Zane Joseph Grabau; Donald W. Dickson (EDIS, 2018)
Nematodes, non-segmented roundworms, can cause serious yield suppression in peanut production. This 10-page fact sheet written by Zane J. Grabau and Donald W. Dickson and published by the UF/IFAS Department of Entomology and Nematology explains how to recognize a potential nematode problem in a peanut production, confirm it with an expert, and choose the best management tools to control the problem. http://edis.ifas.ufl.edu/in1199